VD_FINDINFO Jug / 2014 / 315 vom 26. Mai 2014 - VD Tribunal cantonal (2014)
CONSTATATION DES FAITS, PRÉSOMPTION D'INNOCENCE, VOIES DE FAIT, MENACEDROIT PÉNAL, INJURE, LÉGITIME DÉFENSE, ÉTAT DE NÉCESSITÉ, EXCUSABILITÉ | 47 CO, 126 al. 1 CP, 177 al. 1 CP, 180 al. 1 CP, 10 CPP (CH)